Composite outcomes in observational studies of Crohn's disease: a systematic review and meta-analysis - Catarina Afonso de Santiago Sottomayor (2022)
Background and Aims: This systematic review and meta-analysis aims to assess composite and aggregate outcomes of observational studies in Crohn's disease and to evaluate whether the number and type of variables included affect the frequency of the outcome. Methods: MEDLINE [via PubMed], Scopus, and Web of Science were searched to identify observational studies that enrolled patients with Crohn's disease and evaluated a composite or aggregate outcome. The proportion of patients achieving the outcome was determined and a random-effects meta-analysis was performed to evaluate how the frequency of each outcome varies according to the reporting of predefined variables. Results: From 10257 identified records, 46 were included in the qualitative analysis and 38 in the meta-analysis. The frequency for composite and aggregate outcomes was 0.445 [95% confidence interval (CI) 0.389-0.501] and 0.140 [95% CI 0.000-0.211], respectively. When comparing composite outcomes by number of included variables, the frequency was 0.271 [95% CI 0.000-0.405] and 0.698 [95% CI 0.651-0.746], for one and six variables, respectively. The frequency of the composite outcome varied according to the identity of the variables being reported. Specific pairs of predefined variables had a significant effect in the frequency of composite outcomes. Conclusion: Composite outcomes with increasing number of predefined variables show an increase in frequency. Outcomes including variables such as "Surgery" and "Steroids" had higher frequencies when compared to the ones that did not include these variables. These results show that the frequency of composite outcomes is dependent on the number and type of variables being reported.